Seroprevalence of Hepatitis B Virus, Hepatitis C Virus and Human Immunodeficiency Virus in Children Undergoing Endoscopy in Our Pediatric Gastroenterology Clinic - Deveci, Ugur; Acar, Ufuk (Aves Yayincilik, Ibrahim Kara, 2020)
Objective: There is a risk of infection during interventional procedures such as endoscopy. Therefore, routine tests for infective pathogens before endoscopy and surgical procedures are very important in terms of protecting healthcare workers, determining the infection status of patients, and providing counseling, care and treatment services. The aim of this study was to evaluate the seroprevalence of hepatitis B virus (HBV), hepatitis C virus (HCV) and human immune deficiency virus (HIV) infections of patients who underwent endoscopy. Material and Methods: Demographic data and HBsAg, anti-HBs, anti-HCV and anti-HIV test results of the patients who underwent endoscopy between January 2017 and December 2017 in the pediatric gastroenterology department of our hospital were analyzed retrospectively. Results: Of the 377 cases included in the study, 160 (42.4%) were males and 217 (57.6%) were females, with a mean age of 9.9 +/- 4.6 (range: 1-18) years. Mean ages of the girls and boys were 10.3 +/- 4.7 and 9.4 +/- 4.6 years, respectively (p> 0.05). In our study, chronic hepatitis C was detected in one and chronic hepatitis B infection in one patient. 63.9% of the cases were immune to hepatitis B infection. Conclusion: Seroprevalence of HBsAg, anti-HCV and anti-HIV in our study was not higher than the general population. However, all healthcare personnel should comply with infection control measures during interventional procedures such as endoscopy, regardless of serological examinations of the patients. In addition, patients who do not have protective titer of anti-HBS should be vaccinated, and patients with infection should also be closely followed-up.
Keywords: Endoscopy; hepatitis B virus; hepatitis C virus; human immunodeficiency virus; seroprevalence; infection control